The Role of the Aceh Customary Council in Implementing Hak Langgeh: Navigating Between Sharia and Customary Law - Trisna, Nila; Aulia, Muhammad Reza; Moulia, Nouvan (Universitas Islam Negeri Raden Intan Lampung, 2025)
Aceh, as a region with special autonomy, possesses distinctive authority in implementing Islamic law and customary practices, as stipulated in Law No. 11 of 2006 concerning the Government of Aceh. Among these is Hak Langgeh (Syuf’ah), a customary right derived from Islamic legal traditions and constitutionally recognized. However, discrepancies exist between the normative legal framework and its practical implementation, particularly in land transactions. This study aims to examine the legal status of Hak Langgeh within Aceh’s legal system and to analyse the constitutional and institutional role of the Aceh Customary Council (Majelis Adat Aceh/MAA) in protecting and enforcing this right. Employing a juridical-empirical method with descriptive analysis, the research draws on primary data gathered through interviews with traditional leaders, MAA representatives, village (Gampong) authorities, and parties involved in land disputes. The findings indicate that the MAA plays a significant role in promoting indigenous rights, yet its impact is hindered by limited institutional resources and unclear legal mandates. The study concludes that while the MAA has a constitutional basis in strengthening customary norms, its practical role remains constrained. Reinforcing the legal recognition of Hak Langgeh, enhancing the institutional capacity of the MAA, and harmonizing customary law with Islamic Sharia and national legislation are essential for achieving an integrated and constitutionally aligned legal order in Aceh